Flowering and seeding patterns in unmanaged and managed Nothofagus pumilio south Patagonian forests - Martínez Pastur, Guillermo José (2008)
Regeneration is the success key for the silvicultural treatment implemented in natural seed produced forests. Most of the studies assumed that regeneration is limited by environmental factors and herbivory, but few considered other limiting factors, such as limitants during the flowering and seeding process as bird or insect foraging. It is necessary a whole cycle approach study to understand the bottlenecks in the full regeneration processes. The aim of this work was to analyze the flowering and the seeding patterns in managed and unmanaged stands of Nothofagus pumilio forests, including the pre-dispersion insect and bird foraging analysis, and the abscised biomass production along one growing season. Our results showed that a high percentage of pollinated flowers success in produce fruits (68-79%), independently to the seed rain production and the forest management of the stand (2.2 to 14.7 million.ha-1). The premature abscission of fruits was the main loss factor (13-25%), while biotic factors (insect and bird foraging) was not greatly (less than 5%). The other important loss factor was the large percentage of empty seeds observed in all the treatments (21- 32%), which was significantly greater in primary unmanaged stands. More studies are necessary to explain the causes of these two main loss factors, and self-incompatibility studies to quantify its influence in empty seed production, as well as to extend this kind of studies in long periods of time to include seeding years with different seed rain production.